Seres híbridos del mito clásico y videojuegos. - Macías-Villalobos, Cristóbal (Universidade de Aveiro, 2021)
In video games, the monster almost always acts as an incarnation of evil. It is also an antagonist of the hero and the main obstacle to his success. In this article, we discuss how monsters of classical myth, which are usually hybrid, have been updated in certain Classical‐themed video games, particularly in the different versions of the God of War saga
Hybrid beings of classic myth and video games.
Keywords: Seres fabulosos; Héroes; Mitología clásica; Videojuegos; Monster; Hybrid creatures; Antagonist; Hero; God of War; Video games